Schizophrenia and violent behavior - Valença,Alexandre Martins (2011)
The aim of this study is to report the case of a woman who killed a child. After a forensic psychiatric appraisal to evaluate penal responsibility, she was considered not guilty by reason of insanity and mandatorily committed to the central forensic psychiatric hospital in the State of Rio de Janeiro, Brazil. The patient received a diagnosis of paranoid schizophrenia, based on DSM-IV-TR. She was not in psychiatric treatment and showed psychotic symptoms before the violent behavior became manifest. The study of motivational factors in homicidal behavior may provide further knowledge for understanding, preventing and treating it in such cases.